Wishes and needs of community-dwelling older persons concerning general practice: A qualitative study. - Sophie C E van Blijswijk; Claudia S de Waard; Petra G van Peet; Dagmar Keizer; Margaret von Faber; Margot W M de Waal; Wendy P J den Elzen; Jacobijn Gussekloo; Jeanet W Blom (PLoS ONE, 2018)
Introduction Community-dwelling older persons often experience hindering health complaints that disturb daily activities. If general practitioners (GPs) are unaware of such complaints, this could lead to a mismatch in provided care and needed or expected care. In this qualitative study with community-dwelling older persons we investigated how older persons experience hindering health complaints, how they deal with them, and what they expect from their GP. Methods Participants (aged ≥80 years) with pain and/or problems with walking/standing were invited to participate in a (group)interview about hindering health problems and expectations from general practice. Data were analysed using the framework method and results were discussed with a client panel. Results Participants experienced various hindering health complaints in addition to pain and/or problems with walking/standing. Complaints affecting social activities were experienced as the most hindering. Participants actively tried to remain independent and, to achieve this, GPs were expected to be involved and be easily accessible. However, they did not expect specific help from their GP for pain or problems with walking/standing. Suggestions for improvement of care from GPs included optimisation of accessibility (continuous availability by telephone), a yearly check including medication review, open communication, and empathy and support during major life events. Conclusions According to older persons with hindering health complaints, GPs could improve their accessibility/relationship with patients by: 1) continuous telephonic availability, 2) initiating regular contact with medication reviews, and 3) initiating support during major life events. This might lower the reported barriers to contact the GP for hindering health complaints.